Fauna Names in the Ḍākārṇava - Sinclair, Iain (History of Science in South Asia, 2025)
The Ḍākārṇava, a Buddhist tantra extant since the eleventh century, includes 108 fauna goddesses in its principal maṇḍala. Many of the associated fauna species have not been identified before. This study investigates these zoonyms in light of the tantra’s natural and linguistic environment, located in the medieval coastal northeast of the Indian subcontinent. Drawing on Sanskrit medical and lexical literature, as well as regional zoological data, new identifications are proposed for species including the red-vented bulbul, muntjac deer, dhole, Asian water monitor, and windowpane oyster. Additional names are conjectured to designate the clouded leopard, pangolin, silond catfish, and others. The article includes a revised edition and annotated translation of Ḍākārṇava 15.125cd–129, 135–138, and 167–170ab, along with a concordance of fauna names from directly related tantric texts: the Kulikātattvanirṇaya, Laghutantraṭīkā and Kālacakratantra.